The Emergence of Second‐Tier Auditors in the US: Evidence from Investor Perceptions of Financial Reporting Credibility. (7th March 2013) - Cassell, Cory A.; Giroux, Gary; Myers, Linda A.; Omer, Thomas C.
Abstract We examine changes in the association between auditor type (Big 4, Second‐Tier, and Other non‐Big 4) and perceived financial reporting credibility in the wake of events (e.g., Andersen's failure, the implementation of SOX, creation of the PCAOB, etc.) which led to significant growth in Second‐Tier client portfolios and increased scrutiny of Second‐Tier audit practices. Our results reveal that financial reporting credibility of Second‐Tier clients was lower than that of Big 4 clients and was indistinguishable from that of Other non‐Big 4 clients pre‐Andersen. However, post‐Andersen, we find that financial reporting credibility of Second‐Tier clients is higher than that of Other non‐Big 4 clients and is indistinguishable from that of Big 4 clients. We expect that our results will be of interest to regulators, both in the United States and in the European Union, who have expressed concerns about the current state of competition in the audit market, management and boards of directors that are contemplating switching to a Second‐Tier audit firm, and academics investigating quality differences among audit firm types.